Malignancies in Deceased Organ Donors: The Spanish Experience. Issue 9 (1st April 2022) - Mahíllo, Beatriz; Martín, Silvia; Molano, Esteban; Navarro, Aurora; Castro, Pablo; Pont, Teresa; Andrés, Amado; Galán, Juan; López, Montserrat; Oliver, Eva; Martínez, Adolfo; Mosteiro, Fernando; et al.
Abstract : Background: To better define the risk of malignancy transmission through organ transplantation, we review the Spanish experience on donor malignancies. Methods: We analyzed the outcomes of recipients of organs obtained from deceased donors diagnosed with a malignancy during 2013–2018. The risk of malignancy transmission was classified as proposed by the Council of Europe. Results: Of 10 076 utilized deceased donors, 349 (3.5%) were diagnosed with a malignancy. Of those, 275 had a past (n = 168) or current (n = 107) history of malignancy known before the transplantation of organs into 651 recipients. Ten malignancies met high-risk criteria. No donor-transmitted cancer (DTC) was reported after a median follow-up of 24 (interquartile range [IQR]: 19–25) mo. The other 74 donors were diagnosed with a malignancy after transplantation. Within this group, 64 donors (22 with malignancies of high or unacceptable risk) whose organs were transplanted into 126 recipients did not result in a DTC after a median follow-up of 26 (IQR: 22–37) mo, though a prophylactic transplantectomy was performed in 5 patients. The remaining 10 donors transmitted an occult malignancy to 16 of 25 recipients, consisting of lung cancer (n = 9), duodenal adenocarcinoma (n = 2), renal cell carcinoma (n = 2), extrahepatic cholangiocarcinoma (n = 1), prostate cancer (n = 1), and undifferentiated cancer (n = 1). After a median follow-up of 14 (IQR: 11–24) mo following diagnosis, the evolution was fatal in 9 recipients. In total, of 802 recipients at risk, 16 (2%) developed a DTC, which corresponds to 6 cases per 10 000 organ transplants. Conclusions: Current standards may overestimate the risk of malignancy transmission. DTC is an infrequent but difficult to eliminate complication. Abstract :